CqsA-introduced quorum sensing inhibits type VI secretion system 2 through an OpaR-dependent pathway in Vibrio parahaemolyticus. (January 2022) - Wu, Kui; Long, Yongyan; Liu, Qian; Wang, Wei; Fan, Guoyin; Long, Hui; Zheng, Yangyun; Ni, Xiansheng; Chen, Shengen; Chen, Haiying; Shuai, Shufen
Abstract: The well-known food-borne pathogen Vibrio parahaemolyticus employs at least three quorum sensing signals to maintain its high environmental adaptability. V . parahaemolyticus CqsA, the synthase involved in 3-hydroxyundecan-4-one quorum sensing signal, introduces a quorum sensing network. The V. parahaemolyticus virulent factor type VI secretion system 2 (T6SS2), which is associated with adhesion to host cells, was previously reported to be regulated by a quorum sensing system. Herein, we set out to determine the role of CqsA-introduced quorum sensing (CIQS) in T6SS2-associated virulent regulation. Using a tandem mass tag (TMT)-based quantitative proteomics assay, 17 T6SS2 proteins were found having significantly higher abundances in the Δ cqsA strain than in the wild type strain. TMT proteomics assay results were confirmed by a parallel reaction-monitoring (PRM)-based proteomics assay. Two T6SS2 up-regulators, OpaR and CalR, were found under control of CIQS in the TMT proteomics assay, while OpaR was down-regulated and CalR was up-regulated by CIQS. Thus, it was hypothesized that CIQS would inhibit T6SS2 with an OpaR-dependent mechanism. Epistasis experiment with quantitative PCR was designed to analyze the role of OpaR in the process of CIQS inhibiting T6SS2 production. The mRNA levels of T6SS2 genes were up-regulated in the Δ cqsA strain while down-regulated in the Δ opaR strain and in the Δ cqsA Δ opaR mutant, indicating that OpaR plays a predominant role in the regulation of T6SS2 by CIQS. Using a cell adhesion assay, we further found that the T6SS2-dependent adhesion activity of V. parahaemolyticus to Hela cells was also inhibited by CIQS and the inhibition was OpaR-dependent. In this study, we confirmed that V . parahaemolyticus CIQS inhibited T6SS2 through an OpaR-dependent pathway. It enriches the knowledge of how V. parahaemolyticus quorum sensing regulates its virulence. Highlights: It was confirmed by proteomics methods that CqsA-introduced quorum sensing (CIQS) regulates a lot of proteins production. CIQS inhibits the production of type VI secretion system 2 (T6SS2) and the T6SS2-dependent cell adhesion. CIQS acts as an inhibitor of the master quorum sensing regulator of OpaR and regulates other T6SS2-associated transcriptional factors. CIQS indirectly inhibits T6SS2 through an OpaR-dependent pathway.